Near-real-time nutrition-sensitive fisheries management - Tilley, Alexander; Longobardi, Lorenzo; Bonis-Profumo, Gianna (WorldFish, 2023)
Presentation of PeskAAS system and the novel integration of near-real-time nutrition modelling of catches for use in Timor-Leste fisheries management and food balance sheet